STSHC: secure and trusted scheme for Hadoop cluster. (1st January 2014) - Zhou, Quan; Wu, Daixian; Tang, Chunming; Rong, Chunming
Hadoop is a distributed big data storage and processing framework hugely adopted in different sectors from online media, education, government and social media to handle the enormous growth of information in their respective domains. However, the core architecture of the solution is based on a trusted cluster. It lacks native methods for protecting sensitive data that cross over enterprises and are exposed or accessed illegally. In the paper, this work aims to construct a secure and trusted scheme for Hadoop cluster (STSHC). Firstly, we review the architecture of Hadoop cluster, and discuss the security risks and security requirements. And then we propose a secure and trusted architecture framework for Hadoop cluster with trusted computing base (TCB). Moreover, some protocols, which are the key management, the node trusted management protocol, the client access management protocol, the node access management protocol and job executing management protocol, are designed in detail. Finally, the security analysis shows that the scheme can efficiently meet the security requirement of Hadoop cluster.